DAMPAK PERSELINGKUHAN ORANG TUA TERHADAP PERILAKU SOSIAL ANAK (STUDI KASUS KECAMATAN CEPOGO KABUPATEN BOYOLALI) - Prasidarini, Rifka Ilma; Arifin, Muhammad (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: This research was motivated by the writer’s concern regarding the impact of social behavior on children who commit infedelity in Cepogo District, Boyolali Regency. The aim of this research is to explore the impact experienced by children of parents involved in extramarital affairs on their social behavior, as well as analyze solutions suggested by the shari’ah to evercome this impact. The research method used is qualitative, implementing case study techniques in data collection. The result of the research show (1) there are two factors that cause infidelity to occur, namely internal and external factors, among the internal factors are financial problems, sexual dissatisfaction, and lack of communication. Among the external factors are the influence of close friends, closeness to friends of the opposite sex, and social media. (2) the impact of social behavior experienced by children who commit infidelity in Cepogo District is a lack of self confidence, venting on negative things, emotional disturbances,deep trauma, becoming victims of bullying, decreased interest in learning and lack of affection. (2) the Islamic concept in dealing with these impacts is to instill correct beliefs from an early age, choose good friends for children, provide good role models, instill the dangers of destroying the future, and keep children busy with positive activities.Keywords: Infidelity; Impact; Social Behavior.